Applying Experiential Action Learning Pedagogy to an Intensive Course to Enhance Capacity to Conduct Community-Based Participatory Research. (September 2020) - Coombe, Chris M.; Schulz, Amy J.; Brakefield-Caldwell, Wilma; Gray, Carol; Guzman, J. Ricardo; Kieffer, Edith C.; Lewis, Toby; Reyes, Angela G.; Rowe, Zachary; Israel, Barbara A.
Community-based participatory research (CBPR) is widely recognized as an effective approach to understand and address health inequities. Opportunities for public health practitioners and researchers to engage jointly with community partners in intensive colearning processes can build capacity for CBPR. Using active learning approaches that engage diverse partners can enhance partnership development, competence, and equity. Examination of such pedagogical approaches can strengthen understanding of their contributions to the effectiveness of CBPR capacity-building programs. This article describes a weeklong intensive course carried out by the Detroit Urban Research Center as the foundation for a yearlong training program to build the capacity of community-academic partnership teams to engage in CBPR in their own communities. The in-person CBPR course was developed and implemented by expert academic and community instructors and used an experiential action learning model that integrated CBPR principles and processes. We describe the course content and application of our collaborative, experiential action learning model to course design; present results from participant evaluation of course effectiveness, CBPR competence, and equitable partnership development; and examine the contributions of the pedagogical approach to outcomes central to successful CBPR. The participatory, formative course evaluation used multiple methods that included closed- and open-ended questionnaires to assess instructional effectiveness, participant competence on 12 core components of CBPR, and course impact on partner relationships. Evaluation findings suggest that an experiential action learning approach with attention to colearning, collaboration among diverse instructors and participants, and an environment that fosters and models equitable and trusting relationships can be effective in building CBPR capacity.